Effect of degree of saturation on the shear strength of soils obtained from triaxial test under unconsolidated undrained condition [electronic resource] - 218865 Tan, She Hooi; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2007